The Influence of Human Resource Management On Effectiveness With Performance As A Variabele Mediation At The Airlangga Museum Kediri City - Dita Eka Fitriana; Yogi Yunanto; Desi Kristant (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
This research aims to determine whether there is a significant influence between human resource management on effectiveness and performance as a mediation variable in the airlangga museum of kediri city Based on the results of the t test, it is known that partially the Performance variable (X1) has an influence on the performance of lecturers at the Faculty of Economics, Kadiri Islamic University, and the Effectiveness variable (X1) also has an influence on the Influence of Human Resource Management on the Performance and Effectiveness of the Airlangga Museum, Kediri City. The results of the research show that the Human Resource Management variable has a significant influence on the performance and effectiveness of the Airlangga Museum, Kediri City, because the statistical results of the t test for the leadership style variable obtained a value (t count) 2.694 < (t table) 3.21079 with a significance value of 0.002 > 0.1 and the regression coefficient has a positive value of 0.277.